2010
DOI: 10.1001/archfacial.2009.69
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Satisfaction With Facial Plastic Surgery

Abstract: Despite a priori hypotheses that patients treated for depression might be more pessimistic and rate their satisfaction lower than other patients, patients treated for depression show a trend toward greater satisfaction from facial plastic surgical procedures than those not treated for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
0
16
0
5
Order By: Relevance
“…This is in keeping with our results and suggests that overall satisfaction with cosmesis is likely dependent on many more complex factors than absolute measurements and angles. The importance of other psychosocial factors on overall perception of outcome is a phenomenon that has been identified in other studies of cosmetic surgery outcome …”
Section: Discussionmentioning
confidence: 91%
“…This is in keeping with our results and suggests that overall satisfaction with cosmesis is likely dependent on many more complex factors than absolute measurements and angles. The importance of other psychosocial factors on overall perception of outcome is a phenomenon that has been identified in other studies of cosmetic surgery outcome …”
Section: Discussionmentioning
confidence: 91%
“…Crystal et al [ 19 ] and Bagher et al [ 20 ] reported that parents might be more accepting of SDF if their child was uncooperative, especially on anterior teeth. This finding is important because it shows that parents tend to avoid more severe behavior management strategies, such as general anesthesia or passive restraint, which are viewed as unfavorable [ 34 ]. Clemens et al [ 12 ] stated that child behavior during SDF application was not correlated with subjective parent feelings about the discoloration of teeth.…”
Section: Discussionmentioning
confidence: 99%
“…It is an interviewer-administered questionnaire with 22 items, two for each personality disorder, ie, 11 personality traits/disorders that are subdivided into three groups: group A (paranoid, schizoid, schizotypal), group B (antisocial, narcissistic, histrionic, emotional instability borderline subtype, emotional instability impulsive subtype), and group C (anankastic, dependent, and anxious). 23,24 These subdivisions have been used in different classifications for personality disorders, such as the International Statistical Classification of Diseases and Related Health Problems 10th Revision, Diagnostic and Statistical Manual of Mental Disorders (DSM IV), DSM IV-TR, and DSM 5, on which this scale was based and which has thus grouped personality traits and disorders based on their similarity. 24,25 Each disorder trait has a score range from zero to six 24 ; in this study, a disorder was considered present with a score of six, and a marked trait was considered present with three to five points, while a patient “without disorder” was considered with zero to two points.…”
Section: Methodsmentioning
confidence: 99%